(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A positive self-concept is an important part of a client’s happinessand success. Individuals with a positive self-concept have self-confidence andset goals they can achieve. Achieving their goals reinforces their positiveself-concept. Senior secondary school students are those students who arepreparing for adulthood. It is the time when childhood behaviour &attitudes are being replaced by the attitude & behaviour of an adult. Theactive involvement of their parents in education could lead to theireducational success and thus in improving the dwindling fortunes of oureducational standards. Thus, the investigator decides to conduct a study to seethe effect of gender, type of school from where they are studying, literacylevel of parents, working status of mother, stream, locality, community groupon self-concept among senior secondary school students of Kurukshetradistrict..